Dr. Hossam Yacoub and his role in Iraqi music (Journal of the College of Basic Education, 2023)
Dr. (Hussam Yaqoub) is considered one of the eminent researchers, and one of the first pioneers in the field of academic music research in contemporary Iraq, who left his mark on the march of the scientific movement, and supplied the music library with a rich number of valuable literature and research, and it is really unfortunate that it was not a subject of research and study, And what we have discussed is only a serious attempt to study the life of this great self-made researcher, and to highlight his role in Iraqi music.The research consists of five axes; In the first axis, we discussed the research methodology and previous studies. The second axis dealt with the biography of Dr. Hossam Yacoub; His birth and education, and the journey of science and knowledge resulted in a patent, and work and creativity outside the homeland. And it came in the third axis; His scientific and research achievements, his printed and published writings, his manuscript writings, his research published in peer-reviewed scientific journals, his participation in music conferences, and his published music studies. As for the fourth axis, it dealt with; His achievements at the academic level, his supervision of master's theses, his chairmanship of master's theses discussion committees, his membership in master's theses discussion committees, and his membership in scientific committees. Finally, we concluded the research with the fifth axis, in which we established a number of results, conclusions and recommendations, as well as the sources and references that we relied on in our research.